SAYYID UMAR BAGINDA SARI: Spreader of Islamic Teachings in Tanjung Atap Village - Hudaidah, Hudaidah; Aryanti, Nike (Swarnadwipa, 2024)
Islamization in Indonesia began in the 7th century, with its geographic location focused on the Indo-Malay region. In the 15th century, Islamization began to enter the South Sumatra region, and in various areas, especially in the Ogan Ilir District. Sayyid Umar Baginda Sari became one of the ulama figures who played the role of broadcaster of Islam, namely in the Tanjung Atap Village area, starting in the 16th century. This study aims to discuss and get to know the figure of Sayyid Umar Baginda Sari in the spread of Islamin Tanjung Atap village, find out about his arrival, the programscarried out in spreading Islam and also the members involved inspreading it. This figure is very influential because the village ofTanjung Atap is an area where Islam is spread which is consideredold in South Sumatra. This research was conducted using descriptivequalitative research, namely exploratory and inductive qualitativeresearch. In this research I only describe the research results. Allactivities carried out by the object are seen and observed clearly.